Effect of Environmental Temperature on Immune Response of Broilers - Santin, E. [UNESP]; Maiorka, A. [UNESP]; Polveiro, W. J.C. [UNESP]; Paulillo, A. C. [UNESP]; Laurentiz, A. C. [UNESP]; Borges, S. A. [UNESP]; Fischer Da Silva, A. V. [UNESP] (Elsevier, 2003)
Several studies demonstrate that environmental temperature can influence the immune response of poultry. The objective of this research was to determine at which stage in the life of a bird this effect is greatest. In experiment 1, broiler breeder eggs were incubated at three different temperatures (36.8 ± 0.2, 37.8 ± 0.2, and 38.8 ± 0.2°C) from the 13th day of incubation to hatching. After hatching, birds were raised in thermoneutral temperature. In experiment 2, 144 1-d-old broiler chicks were distributed into three environmental chambers with different temperatures (18 ± 2, 24 ± 2, and 32 ± 2°C). In both experiments, the humoral immune responses to Newcastle disease virus (NDV) and infectious bursal disease (IBDV) were evaluated. NDV and IBDV antibody titers were not significantly different (P > 0.05) among treatments.
Keywords: Broiler; Humoral immunity; Temperature